Effective Cooperation in Ecuador: Judicial Control and Limits to Fiscal Discretion - Cevallos Hurtado , Yasmani Fabián (2026)
The study analyzes the legal institution of effective cooperation in criminal proceedings, aiming to determine the need for its approval by a judge through a formal hearing. The research was conducted using a qualitative approach, with a non-experimental design and a descriptive, dogmatic-legal scope, applying theoretical and empirical methods, as well as interviews with judicial operators. The results show that, according to theory and comparative law, countries such as Argentina and Colombia require judicial authorization in a legalization hearing for the application of effective cooperation, which enhances transparency and trust in the process. Interviews reveal that, in Ecuador, prosecutors retain excessive discretion in assessing and applying this mechanism, demonstrating the need for legislative reform. The study concludes that effective cooperation should be subject to prior judicial approval and verification of the information provided, in order to strengthen the legitimacy and legal certainty of criminal proceedings.